PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS SOFTWARE MACROMEDIA FLASH PADA MATERI LINGKARAN DI MTs SYAMSUL HUDA KEDIRI - Nur Suprihatin Nur; Siti Khabibah (Cartesian: Jurnal Pendidikan Matematika, 2021)
Monotonous learning, many and difficult formulas to understand and the lack of student interest have an impact on low learning scores. So we need an innovation or development in the teaching and learning process of mathematics, one of which is by making innovative learning media. The purpose of this study was to develop learning media using Macromedia Flash software on the circle material of class VIII students of MTs Syamsul Huda Kediri. This type of research is development research that adapts the ADDIE development model. The first step is a needs analysis which will then be used as a reference to proceed to the second stage, namely the product design stage and the preparation of research instruments. After the learning media has been created, the media is then validated by material experts and media experts which will then be tested on students. The results of the assessment from the media expert validator obtained a score of 3.5 in the "valid" category and the material expert validator obtained a score of 3.4 in the "fairly valid" category. ". From the results of the study it can be concluded that this learning media received a negative response from students which was probably caused by the buttons in the learning media based on Macromedia Flash Software that did not work optimally.